Impact of gas humidification and nebulizer position under invasive ventilation: preclinical comparative study of regional aerosol deposition - Yoann Montigaud; Quentin Georges; Lara Leclerc; Anthony Clotagatide; Aurore Louf-Durier; Jérémie Pourchez; Nathalie Prévôt; Sophie Périnel-Ragey (Scientific Reports, 2023)
Abstract Successful aerosol therapy in mechanically ventilated patients depends on multiple factors. Among these, position of nebulizer in ventilator circuit and humidification of inhaled gases can strongly influence the amount of drug deposited in airways. Indeed, the main objective was to preclinically evaluate impact of gas humidification and nebulizer position during invasive mechanical ventilation on whole lung and regional aerosol deposition and losses. Ex vivo porcine respiratory tracts were ventilated in controlled volumetric mode. Two conditions of relative humidity and temperature of inhaled gases were investigated. For each condition, four different positions of vibrating mesh nebulizer were studied: (i) next to the ventilator, (ii) right before humidifier, (iii) 15 cm to the Y-piece adapter and (iv) right after the Y-piece. Aerosol size distribution were calculated using cascade impactor. Nebulized dose, lung regional deposition and losses were assessed by scintigraphy using 99mtechnetium-labeled diethylene-triamine-penta-acetic acid. Mean nebulized dose was 95% ± 6%. For dry conditions, the mean respiratory tract deposited fractions reached 18% (± 4%) next to ventilator and 53% (± 4%) for proximal position. For humidified conditions, it reached 25% (± 3%) prior humidifier, 57% (± 8%) before Y-piece and 43% (± 11%) after this latter. Optimal nebulizer position is proximal before the Y-piece adapter showing a more than two-fold higher lung dose than positions next to the ventilator. Dry conditions are more likely to cause peripheral deposition of aerosols in the lungs. But gas humidification appears hard to interrupt efficiently and safely in clinical use. Considering the impact of optimized positioning, this study argues to maintain humidification.